F18-FDG-PET for recurrent differentiated thyroid cancer: a systematic meta-analysis. (October 2016) - Haslerud, Torjan; Brauckhoff, Katrin; Reisæter, Lars; Küfner Lein, Regina; Heinecke, Achim; Varhaug, Jan Erik; Biermann, Martin
Background: Positron emission tomography (PET) with fluor-18-deoxy-glucose (FDG) is widely used for diagnosing recurrent or metastatic disease in patients with differentiated thyroid cancer (DTC). Purpose: To assess the diagnostic accuracy of FDG-PET for DTC in patients after ablative therapy. Material and Methods: A systematic search was conducted in Medline/PubMed, EMBASE, Cochrane Library, Web of Science, and Open Grey looking for all English-language original articles on the performance of FDG-PET in series of at least 20 patients with DTC having undergone ablative therapy including total thyroidectomy. Diagnostic performance measures were pooled using Reitsma's bivariate model. Results: Thirty-four publications between 1996 and 2014 met the inclusion criteria. Pooled sensitivity and specificity were 79.4% (95% confidence interval [CI], 73.9–84.1) and 79.4% (95% CI, 71.2–85.4), respectively, with an area under the curve of 0.858. Conclusion: F18-FDG-PET is a useful method for detecting recurrent DTC in patients having undergone ablative therapy.